Empowering the Elderly through Simple Self-Care Education: A Community Service Program in Bandung - Intan Putri Utami; Wening Sukmawati; Laila Abdah Shobrina (Jurnal Sentra Pengabdian, 2025)
The aging process is associated with a progressive decline in physical, psychological, and social functions, which increases the vulnerability of older adults to personal hygiene and self-care problems. This community service initiative was designed to empower elderly individuals through educational interventions promoting simple and practical self-care of the hair, eyes, nails, and feet. The program was implemented at the “Juara” Elderly School, Lengkong District, Bandung City, in collaboration with the Indonesian Elderly Association (LLI). A participatory learning approach was adopted, combining interactive lectures, focused group discussions, and direct demonstrations to facilitate experiential learning. Evaluation of pre- and post-education assessments revealed a 35% improvement in participants’ knowledge regarding personal hygiene practices. In addition, qualitative observations indicated increased enthusiasm, confidence, and independence among participants in performing self-care routines. The activity demonstrated that structured health education for the elderly can effectively promote healthy aging, reduce dependency, and enhance overall well-being. The outcomes of this program highlight the importance of community-based participatory approaches in empowering the elderly to maintain dignity and quality of life through improved self-care management.